Sustainability of Remote Work After the Pandemic: The Relationship Between Managerial Support, Flexibility and Employee Satisfaction - Szalai, Szilvia Módosné; Zsarnoczky, Martin Balazs; Poyda-Nosyk, Nina; Vékony, Bence; Dávid, Lóránt Dénes; Csendes, István (Journal of Cultural Analysis and Social Change, 2025)
The COVID-19 pandemic has fundamentally transformed the world of work and accelerated the spread of remote work and hybrid work models. The aim of this study is to explore the organizational and individual factors that influence the effectiveness of hybrid work in the post-pandemic period, as well as how employee satisfaction and work-life balance perceptions have changed. The research was conducted using a mixed methodology: quantitative questionnaire data collection was supplemented by qualitative interviews that examined the differences between managerial and employee perspectives. The results show that hybrid work increases performance and satisfaction when the organization provides clear communication protocols, flexible time frames, and adequate digital infrastructure. At the same time, the decline in face-to-face interactions and the blurring of boundaries have created new sources of stress. We can conclude that the hybrid model is not just a temporary solution, but the basic form of the workplace of the future, based on a balance between efficiency, flexibility, and employee well-being